Efeito do ácido 2-cloroetilfosfônico (ethephon) no amadurecimento de caqui ’fuyu’ e ’rama forte’ - Awad, Marcel; Suzukawa, Y (Revista Ceres, 2025)
Applications of 0, 250, 500 and 1000 ppm of 2-chloroethyl- phosphonic acid (ethephon) by immersion for 2 minutes were tested to degreen persimmon fruits (Diospyros kaki cv.’Fuyu’). The 1,000 and 500 ppm treatments induced complete degreening of the fruits in 3 to 5 days.The 250 and 0 ppm ethephon treatments achieved the same result in 10 to 12 days.